2016
DOI: 10.1017/jfm.2016.169
|View full text |Cite
|
Sign up to set email alerts
|

Droplet–turbulence interaction in a confined polydispersed spray: effect of turbulence on droplet dispersion

Abstract: The effect of entrained air turbulence on dispersion of droplets (with Stokes number based on the Kolmogorov time scale, St η , of the order of 1) in a polydispersed spray is experimentally studied through simultaneous and planar measurements of droplet size, velocity and gas flow velocity (Hardalupas et al., Exp. Fluids, vol. 49, 2010, pp. 417-434). The preferential accumulation of droplets at various measurement locations in the spray was examined by two independent methods viz. counting droplets on images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 61 publications
5
25
0
Order By: Relevance
“…In the present work, measurement of RDF was achieved by ILIDS measurements of droplets. We have verified in our previous work (Sahu et al 2016) that calculation of L c by an RDF based on ILIDS agrees well with the 'droplet counting in a cell' approach (Fessler et al 1994) based on focused spray droplet images. The expression for G in (3.16) is derived for uniform size of droplets in a cloud.…”
Section: Radial Distribution Function (Rdf)supporting
confidence: 77%
See 3 more Smart Citations
“…In the present work, measurement of RDF was achieved by ILIDS measurements of droplets. We have verified in our previous work (Sahu et al 2016) that calculation of L c by an RDF based on ILIDS agrees well with the 'droplet counting in a cell' approach (Fessler et al 1994) based on focused spray droplet images. The expression for G in (3.16) is derived for uniform size of droplets in a cloud.…”
Section: Radial Distribution Function (Rdf)supporting
confidence: 77%
“…Also, the fact that the droplet-gas slip velocity decreases significantly for all droplet sizes far downstream of the injector exit (see Gounder, Kourmatzis & Masri 2012;Sahu et al 2016) further supports the above assumption. However, in our earlier work (Sahu et al 2014a) we have shown that the integral length scale of the droplet flow is smaller than that of the gas flow, and also, the gas velocity fluctuations are smaller than the droplet velocity fluctuations, though the differences are smaller for droplets of low Stokes number.…”
Section: Droplet Velocitysupporting
confidence: 61%
See 2 more Smart Citations
“…The local concentration is measured along the wall-normal plane by counting the number of particle centroids detected. This approach was used for inertial particles in air (Yang & Shy 2005;Sahu et al 2014;Sahu et al 2016) and in water (Kiger & Pan 2002). Knowles & Kiger (2012) showed that, in water, laser-based measurements of particle concentration can be misestimated by as much as 30%; however, they considered volume fractions one order of magnitude higher than the present case.…”
Section: Measurement Methodsmentioning
confidence: 99%